Quality of life meaning for the older adult and his family - Vera, Martha (2007)
Objective: To understand the meaning that the linguistic expression ‘quality of life of the older adult’ has for the olderadultandhisfamily.Design:Qualitative,descriptive, interpretative-comprehensive study, based on the Theory of Social Representations. Setting: Asentamiento Humano LauraCaller,enLosOlivos,Lima,Peru.Participants:Older adults and theirrespective families. Methods: Techniques andinstrumentsconsistedinobservation,in-depthandfocal groupinterviews;observationguideandtwoquestionnaires with eight previously validated open questions. Main outcomemeasures:Qualityoflife significance fortheolder adultandhisfamily.Results:Between2004and2006sixteen olderadultsandtheirrespectivefamilygroupsparticipated. ‘Objectivity’ and ‘anchorage’ speeches and general, ideographic-axial and nomotetic-I analyses allowed the emergency of four social representations: a) knowledge on aging and being an older adult; b)main and secondary elements on older adult quality of life meaning; c) older adult and family values and attitudes on quality of life; and, d) older adult needs as a social being and quality of life.Conclusions:Totheolderadultqualityoflifemeansto have peacefulness and tranquility;to be taken care of and protected by the familywith dignity, love and respect; and associalbeinghavingsatisfiedhisneedsforfreeexpression, decision, communication and information. Forthe family, that the older adultsatisfies hisfeeding, dress, hygiene and house needs.